Genetic classification and geochemical evaluation of Upper Cretaceous carbonate reservoir oils in Dezful Embayment and Abadan Plain, SW Iran - Hossein Saadati; Ali Kadkhodaie; Mehrab Rashidi; Hossein Bahrami; Hashem Sarafdokht; Dmitriy A. Martyushev; Amir Abbass Jahangard (Journal of Petroleum Exploration and Production Technology)
Abstract The Upper Cretaceous carbonate reservoir oils from the Abadan Plain and Dezful Embayment in southwest Iran underwent analysis utilizing GC, GC-MS, and stable carbon isotope methods to elucidate the regional genetic oil family distribution. The study encompassed oil-source rock correlation through biomarker and stable carbon isotope ratios of Sargelu, Garau, Kazhdumi, and Pabdeh rock extracts to assist in establishing the best relevant source rock. Steranes and hopanes thermal maturity parameters were employed to define early maturity to the peak of oil generation level in the potential source rock. Equivalent vitrinite reflectances, estimated using aromatic compounds, suggest these paraffinic-naphthenic to aromatic-intermediate oils expelled from source rocks thermally matured from 0.68 to 0.85% Ro. The findings categorized the studied oils into families A and B. Family A oils, primarily associated with the Abadan Plain reservoirs, demonstrated a prevalence of more reducing conditions with a carbonate input predominance in early mature source rock. Family B oils originated from marl/shale facies in the Dezful Embayment, where the deeper source rock matured up to the peak of oil generation. Both hopanes and regular sterane distribution patterns reveal a contribution of terrigenous organic matter for both families. However, the δ13Csat and δ13Caro ratios demonstrate marine organic matter input predominance. The analysis emphasized the potential significance of the Kazhdumi Formation as the primary source rock for Family B oils in the Dezful Embayment. The Garau Formation was identified as the main candidate source rock, with the Sargelu and Kazhdumi Formations playing secondary roles to some extent in the generation of Family A oils. Additionally, the study underscored the impact of source rock maturity, organofacies, and trap formation timing as crucial factors influencing the geochemical characteristics of these reservoir oils across the studied area.